2014
DOI: 10.1002/14651858.cd004943.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Interventions at caesarean section for reducing the risk of aspiration pneumonitis

Abstract: Background-Aspiration pneumonitis is a syndrome resulting from the inhalation of gastric contents. The incidence in obstetric anaesthesia has fallen, largely due to improved anaesthetic techniques and the increased use of regional anaesthesia at caesarean section. However, aspiration pneumonitis is still a cause of maternal morbidity and mortality, and it is important to use effective prophylaxis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(20 citation statements)
references
References 131 publications
(19 reference statements)
0
19
0
1
Order By: Relevance
“…This study was not designed to assess aspiration risk in this population, and although there were no recorded instances of aspiration when face mask or laryngeal mask airway were used, this complication is rare (up to 1:1,000), so may not be expected in a population of this size; furthermore, aspiration may be unrecognized, which may cause its true incidence to be under-reported in retrospective studies [18,19]. Another potential advantage for regional anesthesia in this population is the avoidance of exposure of the fetus to general anesthetic drugs.…”
Section: Discussionmentioning
confidence: 99%
“…This study was not designed to assess aspiration risk in this population, and although there were no recorded instances of aspiration when face mask or laryngeal mask airway were used, this complication is rare (up to 1:1,000), so may not be expected in a population of this size; furthermore, aspiration may be unrecognized, which may cause its true incidence to be under-reported in retrospective studies [18,19]. Another potential advantage for regional anesthesia in this population is the avoidance of exposure of the fetus to general anesthetic drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the intragastric pH, a recent Cochrane analysis reported that antacids, H 2 -receptor-antagonists and proton-pump antagonists significantly reduced the risk of an intragastric pH of less than 2.5, but this beneficial effect was less consistently reported for gastric volume. When using a single-agent prophylaxis, antacids alone were superior to H 2 -antagonists, which were more effective than proton-pump inhibitors for increasing gastric pH [5]. In some studies, the pH of gastric aspirate was still low despite antacid prophylaxis, what is most probably attributable to suboptimal timing of administration [6].…”
Section: Preparation: Aspiration Prophylaxis and Antibiotic Administrmentioning
confidence: 99%
“…In some studies, the pH of gastric aspirate was still low despite antacid prophylaxis, what is most probably attributable to suboptimal timing of administration [6]. Until now, we still advise the combination of antacids and H 2 -receptor antagonists, as they are relatively well tolerated, inexpensive and probably beneficial in the prevention of aspiration pneumonitis [5]. Experience with protonpump inhibitors in obstetric anaesthesia is scarce.…”
Section: Preparation: Aspiration Prophylaxis and Antibiotic Administrmentioning
confidence: 99%
“…Routine acid aspiration prophylaxis should therefore be administered to all obese parturients undergoing cesarean delivery. In a recent meta-analysis, Paranjothy et al44 reported a significant reduction in the risk of intragastric pH <2.5 with antacids, H 2 antagonists, and proton pump inhibitors, when compared with placebo or no treatment. The combined use of antacids plus H 2 antagonists was associated with a significant reduction in the risk of intragastric pH <2.5 when compared with placebo or with antacids alone.…”
Section: Technical Considerationsmentioning
confidence: 99%
“…The combined use of antacids plus H 2 antagonists was associated with a significant reduction in the risk of intragastric pH <2.5 when compared with placebo or with antacids alone. Addition of metoclopramide might confer additional protection,45 but evidence is limited 44. A meta-analysis involving both obstetric and nonobstetric studies suggested that premedication with ranitidine was more effective than proton pump inhibitors in reducing the volume of gastric secretions and increasing gastric pH 46.…”
Section: Technical Considerationsmentioning
confidence: 99%